2022
DOI: 10.3389/fgene.2022.1021685
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting morphobiometric and genomic variability of African indigenous camel populations-A review

Abstract: Camels (Camelus dromedarius) in Africa are adapted to arid and the semi-arid environmental conditions, and are valuable for meat, milk and fiber production. On account of the growing demand for camels in this continent, there is a need for knowledge on their phenotypic and genetic diversity. This is fundamental to sustainable herd management and utilization including the design of appropriate breeding and conservation strategies. We reviewed studies on the phenotypic and genetic characterization, breeding obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…Ishag et al (2010) reported the SNP 419 C>T in the non-coding region (intron 1) of the GH gene of Kenani, Lahwee, Rashaidi, Anafi, Bishari, and Kabbashi camel breeds of Sudan. This could aid in the determination of genetic relationships among the different camel breeds [26]. Zhang Dongcheng et al [27] found that the genetic diversity of the Cytb gene in Chinese Bactrian camels was rich, and the evolution of the D-loop sequence was in line with neutral selection according to sequencing and analysis.…”
Section: Population Genetic Diversity Analysismentioning
confidence: 99%
“…Ishag et al (2010) reported the SNP 419 C>T in the non-coding region (intron 1) of the GH gene of Kenani, Lahwee, Rashaidi, Anafi, Bishari, and Kabbashi camel breeds of Sudan. This could aid in the determination of genetic relationships among the different camel breeds [26]. Zhang Dongcheng et al [27] found that the genetic diversity of the Cytb gene in Chinese Bactrian camels was rich, and the evolution of the D-loop sequence was in line with neutral selection according to sequencing and analysis.…”
Section: Population Genetic Diversity Analysismentioning
confidence: 99%